Quantitative phosphoproteomics reveals that nestin is a downstream target of dual leucine zipper kinase during retinoic acid-induced neuronal differentiation of Neuro-2a cells - Guillaume St-Cyr; Daniel Garneau; Nicolas Gévry; Richard Blouin (BMC Molecular and Cell Biology)
Abstract Background Dual leucine zipper kinase (DLK) is critical for neurite outgrowth in the developing nervous system and during nerve regeneration, but the underlying mechanisms remain largely unknown. To address this issue, we generated stable shRNA-mediated DLK-depleted Neuro-2a cell lines and analyzed their phosphoproteome after induction of neuronal differentiation by retinoic acid (RA). Results Here, we report the identification of 32 phosphopeptides that exhibited significant differences in relative abundance between control and DLK-depleted cells. Two of the most downregulated phosphopeptides identified after DLK depletion were derived from nestin, a type VI intermediate filament (IF) protein typically expressed in neural progenitor cells. The reduced abundance of these phosphopeptides in response to DLK knockdown was validated using parallel reaction monitoring (PRM)-based quantitative proteomics and paired with a concomitant reduction in nestin mRNA and protein expression, indicating that the decrease in nestin phosphorylation was due to a decrease in total nestin in DLK-depleted cells compared to control cells. This DLK-mediated regulation of nestin expression had no apparent effect on neurite formation because nestin knockdown alone was not sufficient to impair RA-induced neurite extension in parental Neuro-2a cells, and nestin overexpression failed to rescue the neurite outgrowth defect observed in DLK-depleted Neuro-2a cells. Conclusions Together, these results demonstrate that nestin is a novel downstream target of DLK signaling but not a mediator of its ability to promote neurite outgrowth during neuronal differentiation.